Application of Phenol Pretreatment for the Isolation of Rare Actinomycetes from Indonesian Soil - YUDHIE ISTIANTO; RADEN SETYO ADJI KOESOEMOWIDODO; YOSHIO WATANABE; HARDANING PRANAMUDA; BAMBANG MARWOTO (Indonesian Society for microbiology, 2012)
Phenol treatment was applied for isolation of rare Actinomycetes using 25 soil samples collected from Pulau Seribu, Tanjung Redep, Manokwari, and Halmahera. The samples were air-dried and suspended in 1.5 % (w/v) phenol solution at 30 oC for 30 minutes, and subsequently cultured on plates of humic acid-vitamin agar (HVA) medium supplemented with cycloheximide (50 μg/mL) and nystatin (50 μg/mL). A total of 61 isolates were obtained and the most dominant isolates were not Streptomyces (only 24.6%), whereas other genera such as Micromonospora, Actinomadura, Microbispora and Polymorphospora were isolated with ratios of 49.2%, 13.1%, 9.8%, and 3.3%, respectively.